PENGARUH SARANA BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI KELAS X IPS SMA NEGERI 1 KELAYANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Oktaviana, Nur; Gimin, Gimin; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of learning facilities and learning motivation on student learning outcomes in economic subjects class X IPS SMA country 1 Kelayang. The population in this study were students of class X SMA country 1 Kelayang which amounted to 46 people, the sample was obtained by using saturated sampling method as much as 46 respondents. Data collection is done through documentationLearning Outcome and questionnaire Learning Facilities, Learning Motivation. Data analysis method used ismultiple linear regression analysis. The result of this research is (1) the learning facilities have a significant effect on the learning outcomes result which is obtained tcount( 2,800 >ttabel 2,017) and significant value (0,008)<0,05; (2) Learning motivation have a significant impact on student learning outcomes where obtained tcount ( 3,714 ) > ttabel (2,017) and significant value (0,001)< 0,05 ; (3) In silmutan there is a positive or significant influence between learning facilities and learning motivation with learning results, fcount (11,621)> ftabel (3,214) and significant value (0,000) < 0.05. The result of multiple regression research found that the learning facilities and learning motivation have a significant effect on the learning outcomes of 35,1% of the learning outcomes and the rest of 64,9% influenced by other factors outside this study. Multiple regression equation obtained in this research is Y =51,868 + 0,334 X1 + 0, 276 X2.. This means that if the learning facilities (X1) and learning motivation (X2) does not exist then the amount of learning outcomes (Y) of 51,868 and any increase in learning facilities will increase student learning outcomes by 0,334 and any increase in learning motivation it will improve student learning outcomes of 0,275.Keywords: Learning Facilities, Learning Motivation and Learning Outcome